Decreased blood loss reduces postoperative complications in resection for hepatocellular carcinoma. (19th February 2014) - Aramaki, Osamu; Takayama, Tadatoshi; Higaki, Tokio; Nakayama, Hisashi; Ohkubo, Takao; Midorikawa, Yutaka; Moriguchi, Masamichi; Matsuyama, Yutaka
Abstract Background The correlation between blood loss and the risk of postoperative complications was unclear in patients undergoing resection of hepatocellular carcinoma (HCC). Methods We studied 539 patients who had resection of HCC. Postoperative complications were recorded according to the modified Clavien‐Dindo classification. Variables were compared between patients with grade III to V complications and those with no or grade I to II. A spline regression analysis was used to estimate the probability of grade III to V complications. Results Among variables, blood loss (P = 0.0001), operating time (P = 0.0001), blood transfusion (P = 0.0001), and tumor size (P = 0.02) differed significantly between patients with grade III to V and those with no or I to II. Multivariate analysis revealed that the factor most strongly related to complications was blood loss (odds ratio 1.68; 95% confidence interval [CI] 1.45–1.96, P = 0.0001). Spline regression analysis showed that an increase in blood loss was accompanied by increase in the risk of complication; when the estimated probability of grade III to V complications exceeded 50% (95% CI 30.0–70.0), the corresponding blood loss was 820 ml. Conclusion Decrease in blood loss in resection of HCC is accompanied by reduced risk of complications. Surgeons need to minimize blood loss as less as 820 ml.